A novel insertion of a rearranged L1 element in exon 44 of the dystrophin gene: further evidence for possible bias in retroposon integration - Mušová, Zuzana; Hedvičáková, Petra; Mohrmann, Markéta; Tesařová, Markéta; Křepelová, Anna; Zeman, Jiří; Sedláček, Zdeněk (Biochemical and biophysical research communications, 2006)
L1 elements are mammalian retrotransposons contributing to genome evolution and causing rare mutations in human. We describe a de novo insertion of an L1 element into the dystrophin gene resulting in skipping of exon 44 and causing Duchenne muscular dystrophy in a boy. The L1 element was rearranged due to the twin-priming mechanism, but contrary to all described L1 rearrangements the 5' region of the inverted L1 sequence ended within the poly(A) tail of the element. Furthermore, the target site for the insertion was located only 87 bp from the insertion site in another patient described previously. These findings can contribute to the understanding of the mechanisms of L1 element rearrangement, and may support the notion that some subregions of the human genome could be preferred targets for retroelements using the L1 enzymatic machinery.
Keywords: financování organizované; Muscular Dystrophy, Duchenne; Base Sequence; dítě; mapování chromozomů; mutační analýza DNA; Chromosome Mapping; Retroelements; lidé; Molecular Sequence Data; transpozibilní elementy DNA; DNA Mutational Analysis; genetická predispozice k nemoci; Genetic Predisposition to Disease; zkreslení výsledků (epidemiologie); Genetic Variation; Financing, Organized; Bias; molekulární sekvence - údaje; DNA Transposable Elements; Male; retroelementy; Duchennova muskulární dystrofie; Exons; medicína založená na důkazech; dystrofin; sekvence nukleotidů; Dystrophin; exony; Child; mužské pohlaví; genetická variace; Evidence-Based Medicine; Humans